Gut microbiota dysbiosis in patients with hepatitis B virus–induced chronic liver disease covering chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. Issue 2 (29th October 2019) - Zeng, Yongbin; Chen, Shanjian; Fu, Ya; Wu, Wennan; Chen, Tianbin; Chen, Jing; Yang, Bin; Ou, Qishui
Abstract: The information regarding the effect of hepatitis B virus (HBV) infection on gut microbiota and the relationship between gut microbiota dysbiosis and hepatitis B virus–induced chronic liver disease (HBVCLD) is limited. In this study, we aimed at characterizing the gut microbiota composition in the three different stages of hepatitis B virus–induced chronic liver disease patients and healthy individuals. Faecal samples and clinical data were collected from HBVCLD patients and healthy individuals. The 16S rDNA gene amplification products were sequenced. Bioinformatic analysis including alpha diversity and PICRUSt was performed. A total of 19 phyla, 43 classes, 72 orders, 126 families and 225 genera were detected. The beta‐diversity showed a separate clustering of healthy controls and HBVCLD patients covering chronic hepatitis (CHB), liver cirrhosis (LC) and hepatocellular carcinoma (HCC); and gut microbiota of healthy controls was more consistent, whereas those of CHB, LC and HCC varied substantially. The abundance of Firmicutes was lower, and Bacteroidetes was higher in patients with CHB, LC and HCC than in healthy controls. Predicted metagenomics of microbial communities showed an increase in glycan biosynthesis and metabolism‐related genes and lipid metabolism–related genes in HBVCLD than in healthy individuals. Our study suggested that HBVCLD is associated with gut dysbiosis, with characteristics including, a gain in potential bacteria and a loss in potential beneficial bacteria or genes. Further study of CHB, LC and HCC based on microbiota may provide a novel insight into the pathogenesis of HBVCLD as well as a novel treatment strategy.